Implementation of complex engineering problem solving projects in a Malaysian engineering programme - Ling, Jen Hua (Papanda Publishier, 2024)
Accreditation bodies mandate incorporating complex problem-solving (CPS) in engineering programmes on top of outcome-based education. However, its attributes are open to interpretation, leading to a lack of consensus on its implementation in engineering curricula. This paper suggests a solution: having CPS in projects, especially for the courses aligned with CPS-related outcomes. To eliminate ambiguities, the characteristics of complex engineering problems (WP) and complex engineering activities (EA) are restated. This ensures a consistent interpretation of WPs and EAs among educators. CPS projects can be phased into four stages: awareness, adoption, growth, and maturity, followed by continual quality improvement at both the course and programme levels. The entire process can span several years. To stay current with the latest academic and industrial developments, implementation should be completed within one accreditation cycle.